The investigation of different growth and morphological parameters of larvae obtained from cryopreserved northern pike (Esox lucius) sperm - Molnár, József; Várkonyi, Levente; Füzes-Solymosi, Enikő; Birkó-Sulyok, Zita Katalin; Izsák, Tibor; Láng, Levente Zete; Csenki-Bakos, Zsolt (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
Northern pike propagation was performed using fresh and frozen sperm using three different methods (5 ml straw in polystyrene box (P. box) and 5 ml straw, and 10 ml cryotube in a Controlled Rate-Freezer (CRF)). The larvae rearing experiment was maintained for 10 days following hatching. Growth and morphological parameters were recorded at immediately after hatching, at the end of the non-feeding larvae stage and 5 days of feeding larvae stage. Polystyrene box 5 ml (8,45±0,89 mg) and 10 ml cryotube (8,39±1,49 mg) groups showed significantly higher body weight than control (8,11±1,26 mg) and CRF 5 ml (7,87±0,85 mg) group at the immediately after hatching larvae stage. Body length in control (8,22±0,86 mm) and P. box 5 ml (8,37±0,68 mm) significantly differed from CRF 5 ml (8,49±0,67 mm) and from cryotube (8,54±0,66) group at the immediately after hatching larvae stages. A significantly higher Body weight and body length values were recorded in P. box 5 ml (17,38±2,25 mg; 14,83±0,88 mm), CRF 5 ml (17,58±2,18 mg; 14,71±0,69 mm) and cryotube (17,28±1,95 mg; 14,86±0,79 mm) compared to the control group (16,48±2,04 mg; 14,52±0,82 mm) at 5 days of feeding larvae stage. No significant difference was recorded between the control and the cryopreserved groups (CRF 5 ml: 74%, cryotube 74%, P. box. 5 ml: 80%) in larvae survival rate. No significant difference in larvae malformation rate was observed between the control and cryopreserved groups at the different larvae developmental stages.